2017
DOI: 10.1002/ajoc.201700568
|View full text |Cite
|
Sign up to set email alerts
|

Diastereodivergent Henry Reaction for the Stereoselective Construction of Nitrogen‐Containing Tetrasubstituted Carbons: Application to Total Synthesis of Manzacidins A and C

Abstract: β,β‐Disubstituted β‐amino alcohols has been synthesized in a diastereodivergent manner from chiral secondary nitroalkanes as starting materials. In this key Henry reaction, the use of different protecting groups resulted in the diastereoselective construction of the tetrasubstituted carbon stereocenter with different configuration. Based on this methodology, a total synthesis of manzacidins A and C has been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Recently, we have also achieved stereoselctive synthesis of manzacidins A and C based on Henry reaction of chiral nitroalkane 1. 9,10 In this study, we have found that in the key Henry reaction, the use of different protecting groups diastereodivergently produces both isomers of tertiary nitroalkanes 2a and 2b, which could be converted to manzacidins A and C, respectively (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Recently, we have also achieved stereoselctive synthesis of manzacidins A and C based on Henry reaction of chiral nitroalkane 1. 9,10 In this study, we have found that in the key Henry reaction, the use of different protecting groups diastereodivergently produces both isomers of tertiary nitroalkanes 2a and 2b, which could be converted to manzacidins A and C, respectively (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 87%
“…(4S,5R)-7cb (322 mg, 1.06 mmol) was also converted to 4c (284 mg, 0.849 mmol, 80%, 6R/6S = 5:1) according to the same manner as (4S,5R)-7ca. Butoxycarbonyl)amino)-1-hydroxypropan-2-yl)-2,2-dimethyl-1,3-dioxan-5yl)carbamate [9] (4S,5R,6R)-4c (64.4 mg, 0.193 mmol) was dissolved in i-PrOH-AcOH = 2:1 (1.50 mL) at ambient temperature, and resulting solution was treated with Zn dust (125 mg, 1.93 mmol) which was added in 3 portions every hour. The mixture was further stirred at ambient temperature for 3 h. After the period of time, the mixture was filtered through a pad of Celite ® and concentrated in vacuo.…”
Section: Tert-butyl ((4r5s)-4-((r)-1-hydroxy-2-nitropropan-2-yl)-22mentioning
confidence: 99%
See 1 more Smart Citation
“…Their landmark strategy established lactone 5 as an advanced intermediate in 13 steps, which can be converted to the natural product through a highly efficient 54% two-step protocol involving formation of the tetrahydropyrimidine motif, followed by bromopyrrole ester installation (Figure B). Since this seminal work, many approaches have developed or applied new methodology toward 5 , constituting a formal synthesis of manzacidin C (the γ epimer of 5 targeted for manzacidin A) . Although 5 appears structurally underwhelming, a literature survey suggests that approaches to this target remain nontrivial and typically require 13–15 steps.…”
Section: Introductionmentioning
confidence: 99%
“…-Nitroalkenes are representative electron-deficient alkenes that can be used as substrates in various carbon-carbon bond-forming reactions such as the Diels-Alder reaction. 4 During the course of our study on the synthesis of chiral ,-disubstituted -amino acid derivatives, 5 we conjectured that asymmetric Diels-Alder reactions of 3-nitrocoumarins 1 followed by reduction of the nitro and lactone groups might give carbocyclic quaternary amino alcohols 6 in an enantiomerically pure form (Scheme 1).…”
mentioning
confidence: 99%